Demonstration-Based Learning Videos on the Topic of Substance Changes in Elementary Schools - Kadek Bersih; I Gede Margunayasa (Universitas Pendidikan Ganesha, 2021)
Less attractive learning media causes low interest in student learning. So, the need for concrete learning media following the stages of student development. This study aimed to create a valid and practical demonstration-based learning video on changing objects in the fifth grade of elementary school. This research is development research using the 4D model. The subjects of this study were two material experts, two media experts, two practitioners, and five students. The method used in data collection in this study is the rating scale method with an instrument in the form of a rating scale ranging from 1-4. The data obtained were analyzed by calculating the validity index of expert judgment and calculating the average response of practitioners and students. The analysis results showed that the material expert's validity index obtained the lowest score of 0.84 and the highest score was 1 with the very good category. The media expert validity index got the lowest score of 0.67 in the good category, and the highest score was 1, which is in the very good category. The overall average score of the practitioner's response was 3.82, and the student response was 3.78, which was in the very good category. Based on the results of this analysis, demonstration-based instructional video media on the topic of changing objects in fifth-grade elementary schools were declared good and suitable for use in the learning process.